Improving Student Engagement in IPAS Learning Through Storytelling Assisted by Nusantara Board Media Among Third-Grade Students at SDN Kemayoran 2 Bangkalan. - Humayrah Nur Syahida; Florecyta Linares Supriyadi; Robiatul Adawiyah; Moh Rizkon Syafrillah; Agung Setyawan (Literasi Nusantara, 2026)
This study aims to analyze the improvement in students' learning engagement in Natural and Social Sciences (IPAS) through the storytelling method supported by Papan Nusantara learning media. This research employed a classroom action research (CAR) design based on the Kemmis and McTaggart spiral model. It was conducted in two cycles, each comprising the stages of planning, action, observation, and reflection. The subjects were 25 third-grade students at SDN Kemayoran 2 Bangkalan, consisting of 15 boys and 10 girls. Data were collected through observation and documentation using a structured sheet covering five engagement indicators: student attention, oral participation, active involvement in storytelling, collaborative skills, and enthusiasm in using the media. Data were analyzed using a descriptive quantitative approach by calculating the percentage of indicator achievement in each cycle. The results showed a significant and progressive increase at each stage: 28.5% (very low) in the pre-cycle, 54.8% (moderate) in Cycle I, and 85.1% (very high) in Cycle II. These findings confirm that combining the storytelling method with culturally contextual Papan Nusantara media effectively fosters a participatory learning environment. Furthermore, this study demonstrates that narrative-based pedagogy integrated with locally contextualized media enhances active engagement, encouraging teachers to adopt this replicable strategy